2011
DOI: 10.4172/1948-5948.s3-004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Drug Susceptibility Testing Methods: Looking for New Strategies against Resistance Mechanism

Abstract: Biofilm is a reservoir of drug resistant microorganisms that can increase the failure rate of anti-infective therapy and is a public health concern. Antibiofilm drug discovery is necessary for developing new drugs, biocides and wound management protocols. This makes the standardization and implementation of in vitro antibiofilm screening platforms a challenge in the search for new antibiotics, because current antimicrobials are active against planktonic bacteria and have poor diffusion across biofilm matrix. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 90 publications
0
22
0
Order By: Relevance
“…Recently studies [4,5,24] reported the use of biosurfactants as antimicrobial molecules, however due to the differences between planktonic and biofilm physiologies affected by these kind of compounds, this work aimed to evaluating the impact of sophorolipids on cells present in both forms/environments, a behavioural variation that so far seems inconsequential. Standard bacterial inhibition tests are almost exclusively based on planktonic bacterial physiology and not the biofilm physiology, even though these conditions are not readily observed in the natural environment.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently studies [4,5,24] reported the use of biosurfactants as antimicrobial molecules, however due to the differences between planktonic and biofilm physiologies affected by these kind of compounds, this work aimed to evaluating the impact of sophorolipids on cells present in both forms/environments, a behavioural variation that so far seems inconsequential. Standard bacterial inhibition tests are almost exclusively based on planktonic bacterial physiology and not the biofilm physiology, even though these conditions are not readily observed in the natural environment.…”
Section: Discusionmentioning
confidence: 99%
“…Standard bacterial inhibition tests are almost exclusively based on planktonic bacterial physiology and not the biofilm physiology, even though these conditions are not readily observed in the natural environment. The standard planktonic bacterial physiology is typically exemplified by free-living single bacteria with optimal nutrition, gas exchange and agitation (typically 250 rpm) [24,25]. In contrast, the biofilm physiology has multicellular differentiation, multicellular communication, internal architecture and rudimentary fluid transport systems [26,27].…”
Section: Discusionmentioning
confidence: 99%
“…Microbial biofilms represent a distinct bacterial physiology characterised by a multicellular phenotype that is fundamentally different from planktonic bacteria. They have been implicated in chronic and recalcitrant health care-associated infections (Dowd et al 2008), the dissemination of community-acquired diseases (Stewart et al 2012), effective hygienic processing, increased failure rate of anti-infective therapy (Bueno, 2014) and marine water and electronics environments (Lourenco et al 2011). Biofilms that are composed of one species are relatively rare in the majority of the natural environment; rather, microorganisms tend to be found in complex multispecies communities associated with surfaces (Stoodley et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bacterial susceptibility to antibiotics may be associated with metabolic changes accompanying the switch from planktonic to sessile lifestyle and horizontal gene transfer due to the high microbial population density [20]. S. pneumoniae may be the aetiological agent of infection, complications, and death together with the emergence of strains resistant to antibiotics.…”
Section: Discussionmentioning
confidence: 99%